Current Situation and Prospect of Adoptive Cellular Immunotherapy for Malignancies - Dong Zhao PhD; Dantong Zhu PhD; Fei Cai MM; Mingzhe Jiang PhD; Xuefei Liu PhD; Tingting Li MM; Zhendong Zheng PhD (Technology in Cancer Research & Treatment, 2023)
Adoptive cell immunotherapy (ACT) is an innovative promising treatment for tumors. ACT is characterized by the infusion of active anti-tumor immune cells (specific and non-specific) into patients to kill tumor cells either directly or indirectly by stimulating the body's immune system. The patient's (autologous) or a donor's (allogeneic) immune cells are used to improve immune function. Chimeric antigen receptor (CAR) T cells (CAR-T) is a type of ACT that has gained attention. T cells from the peripheral blood are genetically engineered to express CARs that rapidly proliferate and specifically recognize target antigens to exert its anti-tumor effects. Clinical application of CAR-T therapy for hematological tumors has shown good results, but adverse reactions and recurrence limit its applicability. Tumor infiltrating lymphocyte (TIL) therapy is effective for solid tumors. TIL therapy exhibits T cell receptor (TCR) clonality, superior tumor homing ability, and low targeted toxicity, but its successful application is limited to a number of tumors. Regardless, TIL and CAR-T therapies are effective for treating cancer. Additionally, CAR-natural killer (NK), CAR-macrophages (M), and TCR-T therapies are currently being researched. In this review, we highlight the current developments and limitations of several types of ACT.